2000
DOI: 10.1023/a:1026537632468
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: A study was conducted in order to compare soil faunal activity in four experimental farming systems using different tillage, chemical input and crop rotation practices: A conventional system with deep-ploughing (CT), an integrated system with reduced tillage and minimum chemical input (IN), a system with reduced tillage and high chemical input (RT) and a system with minimum tillage and high chemical input (MT). In nine experimental fields with two sampling points each, earthworms were sampled and biogenic stru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(10 citation statements)
references
References 27 publications
1
9
0
Order By: Relevance
“…For example, Van Vliet et al (1993) and Topoliantz et al (2000) found that potworms increase porosity through their tunneling activity and their deposition of fecal pellets, thus preparing micro-sites of high fertility. This activity could also influence the distribution of plant roots in the uppermost centimeter of the soil.…”
Section: Achaeta Aberransmentioning
confidence: 99%
“…For example, Van Vliet et al (1993) and Topoliantz et al (2000) found that potworms increase porosity through their tunneling activity and their deposition of fecal pellets, thus preparing micro-sites of high fertility. This activity could also influence the distribution of plant roots in the uppermost centimeter of the soil.…”
Section: Achaeta Aberransmentioning
confidence: 99%
“…Because root exudation is concentrated at the apices of the roots and at the nodes where lateral roots emerge (Jaeger et al, 1999), root architectural traits determine the expansion of the rhizosphere and exudate fluxes per unit of root biomass. A densely branched root system with high biomass and a rapid turnover thus contributes large quantities of exudates (Van der Krift et al, 2001). The chemistry of rhizodeposits is a key controlling variable of rhizosphere dynamics, as microbial communities may shift their N use efficiency in response to substrate stoichiometry, leading to changes in soil N cycling fluxes (Moorshammer et al, 2014).…”
Section: Rhizodeposition and Plant Traitsmentioning
confidence: 99%
“…Inputs of N through fertilization, BNF, atmospheric deposition, and human and animal waste have been found to be substantially higher than hydrological outputs of N in many studies and at many scales (Howarth et al, 1996;Boyer et al, 2002;Groffman, 2008). There is much uncertainty about the fate of this excess N (Van Breemen et al, 2002). Is it stored in soils or vegetation?…”
Section: Introductionmentioning
confidence: 99%
“…Inputs of N through fertilization, BNF, atmospheric deposition, and human and animal waste have been found to be substantially higher than hydrological outputs of N in many studies and at many scales (Howarth et al, 1996;Boyer et al, 2002;Groffman, 2008). There is much uncertainty about the fate of this excess N (Van Breemen et al, 2002). Is it stored in soils or vegetation?…”
Section: Introductionmentioning
confidence: 99%